1992
DOI: 10.1007/bf02309532
|View full text |Cite
|
Sign up to set email alerts
|

Development of the process conception of function

Abstract: Our goal in this paper is to make two points. First, college students, even those who have taken a fair number of mathematics courses, do not have much of an understanding of the function concept; and second, an epistemological theory we have been developing points to an instructional treatment, using computers, that results in substantial improvements for many students. They seem to develop a process conception of function and are able to use it to do mathematics. After an introductory section we outline, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
21

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(129 citation statements)
references
References 8 publications
2
97
0
21
Order By: Relevance
“…This, of course, is due to students' weak understanding of the concept of function, as has been widely documented (see, for example, [1,29]). …”
Section: But This Naturally Leads To the Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, of course, is due to students' weak understanding of the concept of function, as has been widely documented (see, for example, [1,29]). …”
Section: But This Naturally Leads To the Questionmentioning
confidence: 99%
“…(3) Cubic equations without the second term are reducible to system (1) through the same identity, which, by (1), is reducible to a quadratic equation. And finally, (4) Any general cubic equation is reducible to a cubic equation without the second term through Change of Variable, which, by (3), is reducible to a cubic equation.…”
Section: A Bird's Eye View Of the Unitmentioning
confidence: 99%
“…Bloch, 2003;Breidenbach et al, 1992;Carlson, 1998;Harel & Dubinsky, 1992;Hitt, 1994;Mesa, 2004;Trigueros & Martínez-Planell, 2010),…”
Section: Introductionmentioning
confidence: 99%
“…Research into students' developing function conception has revealed that a view of function as a process that accepts input and produces output (Breidenbach, Dubinsky, Hawks & Nichols, 1992) is essential for the development of a mature image of function. This view has also been shown to be foundational for coordinating images of two variables changing in tandem with each other (Thompson, 1994a;Carlson, 1998).…”
Section: Introductionmentioning
confidence: 99%